Genesis of Proto-Indo Languages in the Light of Neo-Nationalism in India: Problem, Challenges and Possibilities - Santosh Prakash Patil, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
India’s multilingual landscape, characterized by profound linguistic diversity and historical stratification, has long been structured around persistent binary oppositions that shape both linguistic practices and academic discourse. Prominent among these are the hierarchical distinctions between Sanskrit (as the refined, classical, and “cultured” language of sacred texts and elite knowledge) and Prakrit (the “natural,” vernacular forms associated with everyday speech and the masses), as well as the postcolonial tensions between English and indigenous/regional languages. This article interrogates these oppositions not as natural or fixed categories but as constructed hierarchies embedded in cultural, political, and ideological discourses, revealing their instability, mutual interdependence, and role in perpetuating exclusionary structures within Indian languages and knowledge production.
Keywords: Indian Languages; Proto; Genesis; Sanskrit; Prakrit; Aryan; Dravid; Federal State; Nationalism